자기공명 탐상기술(MRT)에 의한 비철금속 가공물의 기공 검출 - 서동만; Dong-man Suh; 문관훈; Kwan-hoon Moon (한국주조공학회지, 2023)
본 연구는 다이캐스팅 과정 중 발생될 수 있는 비철금속 가공품 내부의 기공 결함을 검출할 수 있는 기술 개발을 위해 진행되었다. 해당 연구를 통해 제품 내부에 발생 가능한 기공을 사전에 검출하여 불량 생산품의 유통을 사전에 차단하고 나아가 유통된 제품의 파손으로 발생 가능한 손실을 감소시키는데 기여하고자 한다. This study was conducted to develop technology that can detect stomatal defects inside nonferrous metal products that may occur during die casting processes. Through this research, we intend to detect possible pores in the products in advance, block the distribution of defective products, and contribute to reducing possible losses due to damage to distributed products.